Organogenesis of the digestive system in Neotropical carnivorous freshwater catfish Hemisorubim platyrhynchos (Siluriformes: Pimelodidae) - Faccioli, Claudemir Kuhn [UNESP]; Chedid, Renata Alari [UNESP]; Mori, Ricardo Hideo [UNESP]; Amaral, Antonio Carlos do [UNESP]; Belmont, René Alberto Fuster; Vicentini, Irene Bastos Franceschini [UNESP]; Vicentini, Carlos Alberto [UNESP] (Elsevier, 2016)
The morphological development of the digestive system of Hemisorubim platyrhynchos was studied from the day of hatching until 21. days post-hatching (DPH) using histology, histochemistry and scanning electron microscopy to augment the available knowledge regarding the organogenesis of the digestive system of this carnivorous Neotropical fish. The development of the digestive system was divided into four major stages. Stage I (endotrophic period) starts with hatching and ends with the mouth opening at 2 DPH. The digestive tract originated as a straight undifferentiated tube and ended as an esophagus with goblet cells, an incipient stomach and an intestine divided into the anterior, middle, posterior and rectum. Stage II (endo-exotrophic period) is from the onset of feeding to exhaustion of the yolk at 4 DPH. Stage III is the period in which the larvae rely exclusively on exogenous feeding but still have no functional stomach. Stage IV is an exotrophic period marked by the appearance of gastric glands at 15 DPH. At 20 DPH, the saccular stomach can be observed. Fish growth was largely variable over the time period studied, and the variability was predominant between the period in which the yolk was present and after its exhaustion. The mixed feeding period is short, and the larvae subsequently survive solely by exogenous feeding without a functional stomach for 15. days. During this period, the primary site of digestion is the anterior intestine, which presents with a saccular shape. The accessory glands, liver and pancreas were differentiated at 2 DPH and thus contributed to extracellular digestion. Also observed in the intestine were supranuclear inclusions that could promote intracellular digestion. The rectal columnar epithelium showed scarce goblet cells but had apical mucosubstances that were involved in fecal transit, epithelial protection and in the final absorption of substances. Gastric glands appeared at 15 DPH and, until this period, the larvae should receive live feed and after 15 DPH may be weaned. H. platyrhynchos farmers should also be alert to differences in the size of the fish because this species presents cannibalism and needs to be separated into homogeneous batches.
Keywords: Carnivorous freshwater fish; Larvae; Morphology; Neotropical region